A second case of Diphyllobothriasis in Malaysia - Rohela, M.; Jamaiah, I.; Goh, K.L.; Nissapatorn, V. (2006)
Diphyllobothriasis was first reported in Malaysia in 2002. We are reporting a second case of diphyllobothriasis in Malaysia. The patient was a 37-year-old Chinese male seen at the outpatient clinic with a complaint of passing strands of white color flat worm in his stool. He had no other abdominal complaints. Laboratory and physical examinations were normal. Diphyllobothrium latum was confirmed by examination of the gravid proglottids passed out and the typical operculated eggs expelled from the ruptured proglottids. The patient had a history of eating raw fish. He was treated with a single dose of praziquantel.